Cytochrome b5 plays a dual role in the reaction cycle of cytochrome P450 3A4 during oxidation of the anticancer drug ellipticine - Stiborová, Marie; Indra, Radek; Frei, Eva; Kopečková, Kateřina; Schmeiser, Heinz H; Eckschlager, Tomáš; Adam, Vojtěch; Heger, Zbyněk; Arlt, Volker M; Martínek, Václav (Monatshefte fur chemie, 2017)
ABSTRACT: Ellipticine is an anticancer agent that forms covalent DNA adducts after enzymatic activation by cytochrome P450 (CYP) enzymes, mainly by CYP3A4. This process is one of the most important ellipticine DNA-damaging mechanisms for its antitumor action. Here, we investigated the efficiencies of human hepatic microsomes and human recombinant CYP3A4 expressed with its reductase, NADPH:CYP oxidoreductase (POR), NADH:cytochrome b5 reductase and/or cytochrome b5 in Supersomes™ to oxidize this drug. We also evaluated the effectiveness of coenzymes of two of the microsomal reductases, NADPH as a coenzyme of POR, and NADH as a coenzyme of NADH:cytochrome b5 reductase, to mediate ellipticine oxidation in these enzyme systems. Using HPLC analysis we detected up to five ellipticine metabolites, which were formed by human hepatic microsomes and human CYP3A4 in the presence of NADPH or NADH. Among ellipticine metabolites, 9-hydroxy-, 12-hydroxy-, and 13-hydroxyellipticine were formed by hepatic microsomes as the major metabolites, while 7-hydroxyellipticine and the ellipticine N2-oxide were the minor ones. Human CYP3A4 in Supersomes™ generated only three metabolic products, 9-hydroxy-, 12-hydroxy-, and 13-hydroxyellipticine. Using the 32P-postlabeling method two ellipticine-derived DNA adducts were generated by microsomes and the CYP3A4-Supersome system, both in the presence of NADPH and NADH. These adducts were derived from the reaction of 13-hydroxy- and 12-hydroxyellipticine with deoxyguanosine in DNA. In the presence of NADPH or NADH, cytochrome b5 stimulated the CYP3A4-mediated oxidation of ellipticine, but the stimulation effect differed for individual ellipticine metabolites. This heme protein also stimulated the formation of both ellipticine-DNA adducts. The results demonstrate that cytochrome b5 plays a dual role in the CYP3A4-catalyzed oxidation of ellipticine: (1) cytochrome b5 mediates CYP3A4 catalytic activities by donating the first and second electron to this enzyme in its catalytic cycle, indicating that NADH:cytochrome b5 reductase can substitute NADPH-dependent POR in this enzymatic reaction and (2) cytochrome b5 can act as an allosteric modifier of the CYP3A4 oxygenase.
Keywords: High pressure liquid chromatography; Coenzymes; Enzymes; DNA